CD4(+) Lymphocyte-Mediated Suppression of Cytomegalovirus Expression in Human Astrocytes - Cheeran, Maxim C.-J. (American Society for Microbiology, 2000)
Cytomegalovirus-stimulated CD4(+) lymphocytes from seropositive but not seronegative donors suppressed viral gene expression in primary human astrocytes. This suppressive activity was mediated through soluble factors. These findings suggest that CD4(+) lymphocytes play a role in defense of the brain against cytomegalovirus.